Exploration of Unknown Environment with Ackerman Mobile Robot Using Robot Operating System (ROS) - M.S., Hendriyawan Achmad; Nur Afzan, Murtdza; Nor Anis Aneza, Lokman; Mohd Razali, Daud; Saifudin, Razali; Pebrianti, Dwi (2015)
In this paper, authors present a series of work in order to explore unknown environment consists of path and obstacles with the Ackerman model of wheeled mobile robot (car-like). Robot operating system (ROS) used as a basic operation platform to handle the entire of operation, such as sensor interfacing, 2D/3D mapping, and path planning. ROS is an open source framework and huge construction consist of methods. The Ackerman mobile robot is a car-like robot as commonly sees, and what we have been done in this experiment can be applied to the commercial vehicles as a part of autonomous navigation system which is emerge as big issue nowadays. In this work, we had composed robust existing methods to solve the mapping problem with Ackerman mobile robot. It was concluded that the performance of the proposed work is robust for large mapping within unknown construction building.